2001
DOI: 10.1103/physrevb.64.024521
|View full text |Cite
|
Sign up to set email alerts
|

Lattice anisotropy as the microscopic origin of static stripes in cuprates

Abstract: Structural distortions in cuprate materials offer a microscopic origin for anisotropies in electron transport in the basal plane. Using a real-space Hartree-Fock approach, we consider the ground states of the anisotropic Hubbard (tx = ty) and t-J (tx = ty, Jx = Jy) models. Symmetrical but inhomogeneous ("polaronic") charge structures in the isotropic models are altered even by rather small anisotropies to one-dimensional, stripe-like features. We find two distinct types of stripe, namely uniformly filled, anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
30
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 69 publications
(117 reference statements)
6
30
0
Order By: Relevance
“…(A similar conclusion for fully doped stripes has been reached in Ref. [72].) Finally, we study the effect of the nematicity on the pairing amplitude, shown in Fig.…”
Section: H Y S I C a L R E V I E W L E T T E R Ssupporting
confidence: 81%
See 1 more Smart Citation
“…(A similar conclusion for fully doped stripes has been reached in Ref. [72].) Finally, we study the effect of the nematicity on the pairing amplitude, shown in Fig.…”
Section: H Y S I C a L R E V I E W L E T T E R Ssupporting
confidence: 81%
“…[73][74][75] (and in Ref. [72] for nonsuperconducting stripes). However, we find that at large doping (δ ≳ 0.14) it is the opposite orientation which is preferred, i.e., horizontal stripes.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 91%
“…In brief, the physics that determines the ultimate patterns of competing orders is subtle. For instance, there are striped structures interpreted in terms of actual or incipient orders [19], or attributed to be induced by lattice distortion or impurity-pinning effect [20,21]. To date, the issue of the nature of spatial inhomogeneous phases in cuprates is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently subscribed to the second viewpoint, motivated by the direct experimental connection of lattice structure with stripe formation and suppression of superconductivity. 1 However, the interpretation of striped phases as a consequence of lattice-induced hopping and superexchange anisotropy in the CuO 2 plane leaves some open questions. On the qualitative level, these include the absence of static stripes in orthorhombic YBa 2 Cu 3 O 7−δ (YBCO) systems, while quantitatively they include the value of the relative anisotropies required to stabilize a stripe phase.…”
mentioning
confidence: 99%